On the efficiency of school tracking: a perspective from outcomes in dual VET in Switzerland - Joelle Latina; José V. Ramirez (Journal for Labour Market Research, 2017)
In this paper, we examine the efficiency of the sort done by the Swiss lower secondary school tracking system, looking at students' outcomes in dual vocational education and training (VET)-the most common education type at the upper secondary level in the country. We discuss a simple Ricardian model about the process of school tracking based on the absolute advantage (i.e., the ability) of students in abstract learning, as opposed to contextualised learning which is more decisive in dual VET. The mismatch created by the tracking system for certain types of students is key to explain the relative track effect on outcomes in dual VET. Using administrative panel data for the Canton of Geneva, we estimate a series of zero inflated models. All results support the assumption of a miss-allocation of students to lower secondary school tracks. We thus conclude that the efficiency of the sort related to the tracking system could be improved, were students sorted on the basis of their comparative and not absolute advantage in each form of learning.
Keywords: 20; I21; I28; 330; Dual vocational education and training; Abstract learning; Contextualised learning; Tracking; Zero inflated models